2017
DOI: 10.1126/scitranslmed.aai8269
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aurora kinase A and JAK2 prevents GVHD while maintaining T reg and antitumor CTL function

Abstract: Graft-versus-host disease (GVHD) is a leading cause of nonrelapse mortality after allogeneic hematopoietic cell transplantation. T cell costimulation by CD28 contributes to GVHD, but prevention is incomplete when targeting CD28, downstream mammalian target of rapamycin (mTOR), or Aurora A. Likewise, interleukin-6 (IL-6)-mediated Janus kinase 2 (JAK2) signaling promotes alloreactivity, yet JAK2 inhibition does not eliminate GVHD. We provide evidence that blocking Aurora A and JAK2 in human T cells is synergisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 47 publications
6
76
0
Order By: Relevance
“…Recipient splenic mononuclear cells were isolated for T cell migration surface markers on day diabetic-scid gamma-deficient (NSG) mice received a dorsally positioned, 1-cm 2 , split-thickness human skin graft. After a 30-d rest period, 5 × 10 6 human peripheral blood mononuclear cells (PBMCs), allogeneic to the skin donor, were injected into the mouse (18,27). Mice received pacritinib (100 mg/kg) or vehicle twice a day by oral gavage from day 0 until day +14.…”
Section: Pacritinib Permits the Differentiation Of Suppressive Human-mentioning
confidence: 99%
See 1 more Smart Citation
“…Recipient splenic mononuclear cells were isolated for T cell migration surface markers on day diabetic-scid gamma-deficient (NSG) mice received a dorsally positioned, 1-cm 2 , split-thickness human skin graft. After a 30-d rest period, 5 × 10 6 human peripheral blood mononuclear cells (PBMCs), allogeneic to the skin donor, were injected into the mouse (18,27). Mice received pacritinib (100 mg/kg) or vehicle twice a day by oral gavage from day 0 until day +14.…”
Section: Pacritinib Permits the Differentiation Of Suppressive Human-mentioning
confidence: 99%
“…Moreover, we demonstrate that JAK2 blockade significantly delays skin graft rejection. We have shown that JAK2 blockade abrogates human Th1 and Th17 responses using TG101348 (3,18). TG101348 is now regarded as a tool compound, as its use has been associated with Wernicke encephalopathy caused by off-target inhibition of thiamine uptake (19).…”
mentioning
confidence: 99%
“…Over the past several decades, humanized murine models of xenogeneic GVHD (xGVHD) have been developed via the injection of human peripheral blood mononuclear cells (PBMCs) into severely immunodeficient NOD/Shi-scid IL2rg-null (NOG) or NOD/LtSz-scid IL2rg-null (NSG) mice [23][24][25][26][27][28][29][30][31][32]. These models are T cell dependent, and main triggers of T cell activation and expansion are xenogeneic MHC (H-2) class I and class II molecules [23,30,33,34] and xenogeneic costimulatory signals [27,35].…”
Section: Introductionmentioning
confidence: 99%
“…The final purity of the iTreg (CD4 + , CD127 -, CD25 + , Foxp3 + ) (28,29) product was >90% ( Figure 1A). iTreg function was tested in standard suppression assays against DC-allostimulated T cells (22,23,30). Neither S3I-201 nor DMSO was added to the 5-day suppression assay cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Skin rejection was performed blinded according to standard criteria (26,33,38). Processed spleens cells were phenotyped by flow cytometry for Tregs, Tconv, Th1, Th2, and Th17 cells (22,23,30). IHC was performed on the skin grafts to identify Tregs (CD4 and Foxp3), Th1 (CD4 and T-bet), and Th2 (CD4 and GATA3) and scanned by use of ScanScope XT (Aperio Technologies) with a 200×/0.75 NA objective lens at a rate of 3 minutes per slide via Basler Tri-linear array as described (51).…”
Section: Methodsmentioning
confidence: 99%